Successfully Tracheostomy and Monobloc Advancement with External Frontofacial Distraction Followed by Simultaneous Adenoidectomy, Conchotomy, and Septoplasty in Severe Late Crouzon Syndrome (Medico Legal Update, 2021)
A 10-year-old male patient presented with Severe Late Crouzon Syndrome, with turri-brachycephaly, andsevere exorbitism of both eyes, visual loss, beaked nose and maxilla hypoplasia. The head circumference was54 cm and 90 precentile. Patient had a high arched palate, tonsil hypertrophy and type III malocclusion. Fromthe multidisciplinary meeting, in the first stage it was decided to first secure the airway with Tracheostomythen immediately followed by Monobloc Advancement with External Frontofacial Distraction. Then inthe second stage, after removal of the rigid external distractor, by 9 months after first surgery, the patientunderwent a simultaneous procedures of Adenoidectomy, Conchotomy, and Septoplasty. Thus, after patientgot stable in follow-up, Nasendoscopy and Tracheostomy devices was removed. After 11 months follow-up.Visual function still not getting better. However turri-brachycephaly, exorbitism of both eyes, beaked noseand maxilla hypoplasia, head circumference, arched palate, tonsil hypertrophy and the malocclusion weregetting much reduced, and the patient getting happier and more active.